2018
DOI: 10.1080/09540121.2018.1533223
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of use over time of an oral tablet and a rectal gel for HIV prevention among transgender women and men who have sex with men

Abstract: We examined product adherence among 187 men who have sex with men (MSM), and transgender women (TW), enrolled in MTN-017, a phase II, crossover trial comparing safety and acceptability of oral emtricitabine/tenofovir disoproxil fumarate tablet (daily oral) and tenofovir 1% reducedglycerin gel used rectally (daily gel) or before and after receptive anal intercourse (RAI) (rectal gel) for HIV prevention in the US, Thailand, Peru and South Africa. Participants reported adherence via daily text messages during 8-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Using latent class trajectory analyses, we were able to understand differences in participants’ RM use trajectories using their SMS self-reports. Similar to prior research on rectal gel use for HIV prevention among transgender women and MSM [ 17 ], we found our sample could be characterized based on their product use over time. We observed two group-based trajectories across the three modalities, with the two trajectories being distinguished by the quantity of product usage reported per week.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using latent class trajectory analyses, we were able to understand differences in participants’ RM use trajectories using their SMS self-reports. Similar to prior research on rectal gel use for HIV prevention among transgender women and MSM [ 17 ], we found our sample could be characterized based on their product use over time. We observed two group-based trajectories across the three modalities, with the two trajectories being distinguished by the quantity of product usage reported per week.…”
Section: Discussionsupporting
confidence: 59%
“…We examined whether participants’ use of each placebo modality (douche, insert, and suppository) changed over time. Given prior research noting the presence of diverse trajectories [ 16 , 17 ], we hypothesized that we would observe at least two trajectories for each product: one noting an increase in product use over time, and another indicating consistent product use over time. We then examined whether RM product use was associated with participants’ baseline sociodemographic characteristics and sexual behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize trajectory groups identified using GBTM, univariable, and multi-variable ordinal logistic regression models were developed. Predictors considered in the analyses included: age at first dispensing (<25, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], and !45 years); sexual identity (gay/ homosexual, bisexual, and heterosexual/other); country of birth (Australia; other high-income English speaking countries, including Canada, Ireland, New Zealand, United Kingdom, and United States; Asian countries; and other); published estimates of the proportion of males identifying as gay in the postcode of residence (!20%, 10-20%, 5-9%, and <5%) [17]; a recent diagnosis (last 3 months) of rectal gonorrhoea, rectal chlamydia, or infectious syphilis as assessed at study baseline; and recent use of crystal methamphetamine. Variables with a P value of <0.10 in univariable analysis were included in multivariable analysis to allow adjustment for confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Based on quarterly MPR, patterns of PrEP adherence trajectory identified using GBTM were strongly associated with HIV incidence. Internationally, two much smaller cohort studies with shorter follow-up used the GBTM method to summarise PrEP adherence which had been determined by daily text messages to participants [25,26]. One of the studies followed 181 men in California for a total of 48 weeks and reported that the four adherence trajectories identified were highly associated with TDF/FTC concentration in blood samples [27].…”
Section: Adherence Trajectorymentioning
confidence: 99%
“…Long-acting injectable (LAI) forms of PrEP have also been shown to be popular as a potential administrative method [3,6,7], and LAI was recently found to be efficacious in preventing HIV infection [8]. The sparse but emerging literature on product preferences speaks to the need to prepare for a host of potential products and varying preferences among MSM, and a particular need for quantitative research in a large and diverse sample of MSM [6,9,10]. In this study, we assess self-reported likelihood of using various HIV prevention products, including a LAI form of PrEP and sexual event-based pills, gels and anal suppositories among a large and diverse sample of MSM in three US cities.…”
Section: Introductionmentioning
confidence: 99%